A Post-reform Empirical Analysis of Public Social Expenditure of Centre and States in India - Naveen,; Verma, N. M. P. (Advances in Social Sciences Research Journal, 2023)
The need to increase public social expenditure was felt and prescribed by many policy experts even during the decades preceding the reforms. Given the historical opportunity to build a robust national pool of productive human capital, the advocacy for increasing public social expenditure was both inevitable and strategic. This paper attempts to enquire the trends and patterns of public social expenditure in India during the post reform period, the phase characterized with greater potential of realizing demographic dividend in the country’s history. The empirical analysis concerning budgetary allocations towards the social sector incurred by both, the central and state governments under the broad head of expenditure termed as ‘Social Services’ covers within it various sub-components. The analysis of data includes annual budgetary allocations of public financial resources against various components of social services as a percentage of total central expenditure, all state’s total expenditure and GDP. CAGR for all components of social services is calculated for the thirty-year period separately for the centre and states. The evidence suggests that public social expenditure has almost been stagnant during the period as a proportion of GDP which is reflected through qualitative deficiency and quantitative inadequacy particularly in the case of key components of social services such as health and education. Such stagnation of public social expenditure contradicts the policy stance very often advocated and extended by the academia, civil society, bureaucracy and the political class.